Mastering fractions and innovating with the station rotation model in blended learning - Nurul Harizah Abdul Latif; Masitah Shahrill; Wahyu Hidayat (IKIP Siliwangi and I-MES, 2024)
This study explores the effectiveness of the Station Rotation Model (SRM) in adding and subtracting fractions. A mixed-method design was conducted through convenience sampling of 31 students from Year 9. They were given pre-and post-tests consisting of ten questions for collecting quantitative data. Students’ online questionnaires consisting of five-point Likert scales, two open-ended questions, and structured interviews with six selected students were further analysed to collect qualitative data. A non-parametric test was adopted to compare the results of the achievement tests. Wilcoxon’s signed rank test findings showed a significant difference (p=0.024) and a large effect size (rb=0.558) between the achievement test scores. This indicates that the SRM positively impacts students’ performance in adding and subtracting fractions. Three major themes emerged from the questionnaires and interviews about students’ perception of using SRM: Manipulatives make learning fun, enjoyment of working in a group, and challenges in implementing the SRM. Overall, students positively viewed their experiences with the SRM as an approach to teaching and learning. The study offers insights into SRM’s impact on student learning, aiding educators amd researchers assess its future application, especially in mathematics education.